2022
DOI: 10.1083/jcb.202207147
|View full text |Cite
|
Sign up to set email alerts
|

A novel function for the sperm adhesion protein IZUMO1 in cell–cell fusion

Abstract: Mammalian sperm–egg adhesion depends on the trans-interaction between the sperm-specific type I glycoprotein IZUMO1 and its oocyte-specific GPI-anchored receptor JUNO. However, the mechanisms and proteins (fusogens) that mediate the following step of gamete fusion remain unknown. Using live imaging and content mixing assays in a heterologous system and structure-guided mutagenesis, we unveil an unexpected function for IZUMO1 in cell-to-cell fusion. We show that IZUMO1 alone is sufficient to induce fusion, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 99 publications
1
29
0
Order By: Relevance
“…A recent article reported that the tryptophan at position 148 of IZUMO1 was crucial for the binding with JUNO (Brukman et al., 2023). This position is not affected by positive selection and is completely conserved in all Carnivora species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent article reported that the tryptophan at position 148 of IZUMO1 was crucial for the binding with JUNO (Brukman et al., 2023). This position is not affected by positive selection and is completely conserved in all Carnivora species.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between JUNO and IZUMO1 is essential for sperm to dock to the surface of an egg (Bianchi et al., 2014), a crucial recognition step prior to membrane fusion (Inoue et al., 2015). Although neither protein has been conclusively shown to be a fusogen, there is recent evidence that IZUMO1 may have fusogenic activity (Brukman et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian sperm‐egg adhesion is believed to depend on the transinteraction between the sperm‐specific IZUMO1 and oocyte‐specific GPI‐anchored receptor JUNO 31 . A reduction in fusion occurs when sperm are treated with antibodies against IZUMO1, 30 and artificially expressed IZUMO1 induces cell‐to‐cell fusion in cultured somatic cells 32 . These findings indicate that IZUMO1 acts as a fusogen that is physiologically restrictively expressed in sperm cells during fertilization.…”
Section: Discussionmentioning
confidence: 99%
“…A recent article reported that the tryptophan at position 148 of IZUMO1 was crucial for the binding with JUNO (Brukman et al, 2023). This position is not affected by positive selection and is completely conserved in all Carnivora species.…”
Section: Discussionmentioning
confidence: 99%